Indirect suppression of CD4 T cell activation through LAG-3-mediated trans-endocytosis of MHC class II - Ei Wakamatsu; Hiroaki Machiyama; Hiroko Toyota; Arata Takeuchi; Ryuji Hashimoto; Haruo Kozono; Tadashi Yokosuka (2024)
Blockade of immune checkpoint receptors has shown outstanding efficacy for tumor immunotherapy. Promising treatment with anti-lymphocyte-activation gene-3 (LAG-3) has already been recognized as the next efficacious treatment, but there is still limited understanding of the mechanism of LAG-3-mediated immune suppression. Here, utilizing high-resolution molecular imaging, we find a mechanism of CD4 T cell suppression via LAG-3, in which LAG-3-bound major histocompatibility complex (MHC) class II molecules on antigen-presenting cells (APCs) gather at the central region of an immunological synapse and are trans-endocytosed by T cell receptor-driven internalization motility toward CD4 and CD8 T cells expressing LAG-3. Downregulation of MHC class II molecules on APCs thus results in the attenuation of their antigen-presentation function and impairment of CD4 T cell activation. From these data, anti-LAG-3 treatment is suggested to have potency to directly block the inhibitory signaling via LAG-3 and simultaneously reduce MHC class II expression on APCs by LAG-3-mediated trans-endocytosis for recovery from T cell exhaustion.